It's a big world after all - Steven Brakman; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2007)
Thomas Friedman's book the world is flat has been a bestseller since it appeared in 2005. The remarkable success of the book reflects to a certain extent the present fears with respect to increasing globalization. Using many examples, Friedman argues that distance (however defined) is no longer a dominant characteristic of the world economy, or will cease to be so in the very near future. Competition is thought to be a race to the bottom, with the lowest-wage countries as the big winners. We disagree, and with us many other economists (see, for example, Leamer, 2006). Distance dominates all aspects of international trade and many stylized facts of international trade can only be understood by pointing towards the importance of distance. Furthermore, there is little evidence of income convergence. Using various methods and data sets, we show that many threats of global competition for the position of the traditionally developed (OECD) countries are unwarranted.
Keywords: E00; F00; N00; O00; 330; Globalisierung; Entfernung; Außenwirtschaft; Standortwettbewerb; Entwicklungskonvergenz; Kritik; Welt